The clutch structure of pleurodema tucumanum (anura: leptodactylidae) - Ferraro, Daiana Paola (2016)
Anurans have a vast diversity of reproductive mode, and foam nests are a particularly peculiar mode of oviposition. The genus Pleurodema (Anura, Leptodactylidae) includes 15 species with four known oviposition modes. The clutch of Pleurodema tucumanum was described as gelatinous, ovoid plate-like masses, in which eggs are accommodated along a single plane. In this paper, we describe the clutch structure of P. tucumanum based on lab and field observations, and provide notes on the oviducts based on histological sections. Our observations indicate that during amplexus the male of P. tucumanum builds a nest by beating female oviductal secretions, but this nest soon coalesces into a superficial plate-like mass.